Peri-Implantitis - Miriam Ting; Jon B. Suzuki (Dentistry Journal, 2024)
Peri-implantitis can affect the longevity of successfully integrated implants. Implant success is dependent on reducing the peri-implantitis risk or successfully managing peri-implantitis. Further understanding of peri-implantitis can be derived from its prevalence, microbial and diagnostic findings, existing therapies, and the effects of systemic health issues and medication. Based on published information: (1) peri-implantitis is higher in patients who have periodontitis or smoke as well as in implants with 5 years of function; (2) peri-implantitis microflora is different from periodontitis; (3) peri-implantitis risk is increased in patients with cardiovascular diseases and uncontrolled diabetes; (4) most reported peri-implantitis therapies may result in resolution, but the best peri-implantitis treatment is still to be determined; (5) more frequent peri-implant maintenance may reduce risk for peri-implantitis.